Association between healthcare practitioners' beliefs about statins and patients' beliefs and adherence. Issue 3 (26th July 2020) - Huiskes, Victor J.B.; van den Ende, Cornelia H.M.; van Dijk, Liset; Burger, David M.; van den Bemt, Bartholomeus J.F.
Abstract : Aims: Adherence to statins ranges from 32% to 79%. Patients' beliefs about medication are associated with adherence. There is lack of insight into the possible association between beliefs of healthcare practitioners (HCPs) about statins and patients' beliefs and adherence. This study aims to examine whether HCPs' beliefs about statins are associated with patients' beliefs and adherence about/to statins. Methods: Cross‐sectional study in 48 pharmacies and affiliated physicians' practices between 3 September 2014 and 20 March 2015. HCPs' (prescribers and pharmacy staff) and patients' beliefs about statins were assessed with the Beliefs about Medicine Questionnaire (BMQ) specific. Adherence to statins was assessed with the MARS‐5 questionnaire. Multilevel regression analysis was performed to assess the association between HCPs' beliefs and patients' beliefs and adherence. Results: 1504 patients (mean age 66.8 [s.d. ± 9.9] years, 46.5% female) and 734 HCPs (209 physicians, 118 pharmacists and 366 pharmacy technicians) participated in this study. Patients have higher BMQ necessity (16.9 [s.d. ± 4.3]) and BMQ concern (12.3 [s.d. ± 3.9]) scores than HCPs (15.0 [s.d. ± 3.0] and 11.5 [s.d. ± 2.9], P < 0.001). No associations were found between any of the HCPs' BMQ and patients' BMQ scores and adherence to statins. Patients' BMQ necessity, concern and necessity‐concerns (NC)‐differential scores were associated with patients' adherence (MARS‐5) scores. B (95% CI) coefficients were 0.057 (0.035‐0.079), −0.040 (−0.064 to –0.016) and.061 (0.043‐0.079). Conclusions: Patients have stronger beliefs about medication compared to HCPs. No associations were found between HCPs' BMQ scores on the one hand and patients' BMQ scores and adherence to statins on the other hand.